A policy analysis of sleep-related legislation for Canadian licensed childcare facilities - Wendy A. Hall; Melissa Moynihan; Graham J. Reid; Robin McMillan (BMC Public Health, 2024)
Abstract Background National legislative guidelines for sleep and rest are lacking in the Canadian licensed childcare sector. No review of Canadian legislation for licensed childcare facilities has focused on sleep. This paper provides a review of the Canadian provincial and territorial legislative landscape, regarding sleep, rest, and naps in licensed childcare centers. Methods Childcare statutes and regulations for each province and territory were identified and downloaded on a particular date. Statutes and regulations were reviewed focusing on sections articulating licensed childcare facility mandates governing sleep, rest, naps, and sleep equipment. An excel file was used to facilitate systematic data retrieval and comparisons across provinces and territories. Two authors developed and discussed themes that summarized data from the documents. Results No statutes indicated recommendations for sleep, rest, or naps. Only one regulation defined rest (Alberta). Our analysis of regulations identified four themes representing sleep, rest, and naps: programming (general programming, daily programming); space (dedicated space, amount of space, age-specific space); equipment (developmental appropriateness, acceptable sleep equipment, age-specific equipment); and safety (staffing during sleep/rest, sleep position, sleep monitoring, sleep equipment safety, prohibited practices). In Canada, minimal regulatory consistency is evident in required sleep programming, space, acceptability of sleep equipment, and sleep safety considerations. Most jurisdictions’ regulations indicated necessity for developmentally appropriate rest or sleep areas and equipment, in particular for infants, but there was minimal consistency in defining infant age groups. Conclusions Although we identified themes related to sleep across regulations, childcare regulations differ in their definitions of infants and specifications for children’s sleep and rest in licensed Canadian childcare facilities. Without adequate definitions in legislative components of appropriate sleep duration linked to children’s developmental stages, childcare facilities lack guidance to support healthy sleep for children in their care. Future research can examine translation of healthy sleep guidelines into government legislation and mandates for sleep, rest, and naps among young children in licensed childcare.